Sulforaphane protected the injury of human vascular endothelial cell induced by LPC through up-regulating endogenous antioxidants and phase II enzymes. Issue 6 (10th June 2015) - Li, Baolong; Tian, Sicong; Liu, Xu; He, Canxia; Ding, Zhongqing; Shan, Yujuan
<x xml:space="preserve">Abstract</x> Sulforaphane (SFN), which is an isothiocyanate (ITC) that is found in cruciferous vegetables, has received considerable attention because of its beneficial effects.